Sustainable development in the Yellow River Basin: Issues and strategies. (1st August 2020) - Chen, Yi-ping; Fu, Bo-jie; Zhao, Yan; Wang, Kai-bo; Zhao, Meng M.; Ma, Ji-fu; Wu, Jun-Hua; Xu, Chen; Liu, Wan-gang; Wang, Hong
Abstract: The Yellow River is an important water source for north China, which is the fifth largest river all over the world. Here the upstream, midstream and downstream of the Yellow River were selected as case study for well understanding the sustainability of water quality and quantity. The results showed the runoff of Yellow River has decreased since the 1950s due to human activities. Moreover, the water quality of the Yellow River is deteriorating with the rapid development of industry and urbanization. Especially heavy metals pollution, the concentrations of arsenic, cadmium, lead and total nitrogen increased gradually from upstream to downstream, while the concentrations of chromium, mercury, zinc and total phosphorous were highest in the midstream. The concentrations of nitrogen (e.g. ammonium and nitrate), volatile phenol and total amount of Escherichia coli displayed decreasing trends from upstream to downstream. In addition, the concentrations of heavy metals showed the highest value in the corresponding farmland of midstream except for Pb, which displayed the significant positive correlation with yellow river water, moreover As and Cr also showed the carcinogenic risk in irrigated farmland. Further analysis found the agriculture, industry and urban residential areas accounted for influence of 40%, 26%, and 16% on water amount reduce, respectively. Industrial wastewater, domestic wastewater, phosphorus and nitrigen accounted for 66%, 21%, 8% and 5% of the influence on water quality, respectively. The results suggested that the sustainability of the water resource of the Yellow River is at risk in terms of quality and quantity. There is an urgent need to readjust the water allocation plan (namely 87 plan), establishing a water rights trading system, implement the precision irrigation on agricultural practices and adjust the industrial structure of the Yellow River Basin. Graphical abstract: Image 1 Highlights: Runoff of the Yellow River has decreased since the 1950s due to human activities(HA). Water quality of the Yellow River is deteriorating with the rapid development. As, Pb and Cr showed the health risk for human in the water of the Yellow River. As and Cr also showed the carcinogenic risk in corresponding irrigated farmland. Water resource sustainability is at risk in the Yellow River due to human activities.